Efektifitas Penerapan Terapi Slow Deep Breathing terhadap Penurunan Intensitas Nyeri dan Tekanan Darah pada Pasien Hipertensi - Titin Supriatin; Nova Nurfaida; Ruswati Ruswati (Jurnal Siti Rufaidah, 2025)
Hypertension is a global health problem that plays a major role as a leading cause of premature death because it can lead to various serious cardiovascular complications, such as stroke, heart failure, and chronic kidney disease. This condition is often characterized by complaints of severe headaches, especially in the nape of the neck, due to increased blood flow to the brain. In addition to medical therapy in the form of antihypertensive drugs, complementary therapies are also needed to support blood pressure reduction and improve the patient's quality of life. One method that has proven effective is slow deep breathing, a slow, deep breathing technique that helps activate the parasympathetic nervous system, reduce sympathetic activity, improve tissue oxygenation, and produce a relaxation effect that is beneficial in lowering blood pressure and reducing pain. This paper aims to describe the experience of nursing care for hypertensive patients using slow deep breathing therapy. The research method used is a quantitative descriptive with a case report design that is carried out through the stages of assessment, establishing a nursing diagnosis, intervention, implementation, and evaluation. Research data were obtained through interviews, direct observation, and physical examination. The results showed that after three consecutive days of therapy, the patient's pain scale decreased from 5 (moderate pain category) to 2 (mild pain category), while blood pressure, which was initially at 196/122 mmHg, successfully decreased to 140/90 mmHg. These results indicate that slow deep breathing plays an important role in lowering blood pressure and improving the comfort of hypertensive patients. In conclusion, slow deep breathing can be used as a simple, safe, inexpensive, and effective non-pharmacological intervention, and is highly recommended for patients to practice independently in their daily lives to prevent worsening hypertension and optimize disease control efforts.